SCHOOL MATH FESTIVAL - Kondaurova, I.K; Ivanchuk, Y.V (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2019)
The definition of the mathematical festival as several united by some common idea and held with a specific purpose and frequency of competitions in mathematics students is clarified in the article. The structure of the mathematical festival and the requirements for its organization are characterized. One of the main requirements is the creation of the festival Regulations. Methodological support of the mathematical festival for students in grades 5-11 (games «Junior scholar», «Senior scholar», «Railway», team intellectual and entertainment competition, puzzle Games; competition «Journey into the history of mathematics») is considered. The plan of the team intellectual and entertaining competition is given. The results of the article can be used in educational institutions and organizations of additional education to improve the efficiency of the educational process.